La pugna por el diamante. La institucionalización del béisbol capitalino, 1920-1930 - Esparza, Miguel (El Colegio de México, A.C., 2019)
The primary objective of this article is to study how baseball was organized, promoted and developed with the leadership and support of an athletic association in the years between 1920 and 1930. Athletic institutions are spaces that construct power relationships, and so this article will analyze the developments, strategies and actions that founded the sporting organizations controlling the athletics and finances of Mexico City baseball.